Proprietary information and the cost of bank debt. Issue 1 (7th July 2020) - Na, HyunJun
Abstract : Purpose: This study explores how the firm's proprietary information has an impact on the bank loan contracts. It explains the propensity of using the competitive bid option (CBO) in the syndicate loans to solicit the best bid for innovative firms and how it changes based on industry competition and the degree of innovations. This research also examines how the interstate banking deregulation (Interstate Banking and Branching Efficiency Act) in 1994 affected the private loan contracts for innovative borrowers. Design/methodology/approach: The study uses various econometric analyses. First, it uses the propensity score matching analysis to see the impact of patents on pricing terms. Second, it uses the two-stage least square (2SLS) analysis by implementing the litigation and non-NYSE variables. Finally, it studies the impact of the policy change of the Interstate Banking and Branching Efficiency Act of 1994 on the bank loan contracts. Findings: Firms with more proprietary information pays more annual facility fees but less other fees. The patents are the primary determinants of the usage of CBO in the syndicate loans to solicit the best bid. While innovative firms can have better contract conditions by the CBO, firms with more proprietary information will less likely to use the CBO option to minimize the leakage of private information and the severe monitoring from the banks. Finally, more proprietary information lowered the loan spread for firms dependent on the external capital after the interstate banking deregulation. Originality/value: The findings of this research will help senior executives with responsibility for financing their innovative projects. In addition, these findings should prove helpful for the lawmakers to boost economies.